스마트 인솔의 족저압 측정 결과에 대한 타당도 및 신뢰도 평가 - 강호원; 안예린; 김대유; 이동오; 박길영; 이동연; Kang, Ho Won; An, Yae Lynn; Kim, Dae-Yoo; Lee, Dong-Oh; Park, Gil Young; Lee, Dong Yeon (대한족부족관절학회지, 2022)
Purpose: Smart insoles are wearable devices that are inserted into shoes. Smart insoles with built-in pressure and acceleration sensors can measure the plantar pressure, stride length, and walking speed. This study evaluated the validity and reliability of the plantar pressure measurements of smart insoles during walking on flat ground. Materials and Methods: Twenty one subjects were included in this study. After wearing smart insoles, I-SOL® (Gilon, Seongnam, Korea), the subjects walked a 10 m corridor six times at a rate of 100 steps/min, and the middle three steps, free from direction changes, were chosen for data analysis. The same protocol was repeated after wearing Pedar-X (Novel Corporation, Munich, Germany), an insoletype plantar pressure measurement equipment with proven validity. The average maximum pressure (Ppeak, kPa) and the time at which Ppeak appeared (Ptime, %stride) were calculated for each device. The validity of smart insoles was evaluated by using the interclass correlation coefficient (ICC) of Ppeak and Ptime between the two instruments, and Cronbach's alpha was obtained from the Ppeak values to evaluate the reliability. Results: The ICC of Ppeak was 0.651 (good) in the hallux, 0.744 (good) in the medial forefoot, 0.839 (excellent) in the lateral forefoot, and 0.854 (excellent) in the hindfoot. The ICC of Ptime showed 0.868 (excellent) in the hallux, 0.892 (excellent) in the medial forefoot, 0.721 (good) in the lateral forefoot, and 0.832 (excellent) in the hindfoot. All ICC values showed good or excellent results. The Cronbach's alpha of Ppeak measured in the smart insoles was 0.990 in the hallux, 0.961 in the medial forefoot, 0.973 in the lateral forefoot, and 0.995 in the hindfoot; all indicated excellent reliability in all areas. Conclusion: The plantar pressure measurements of smart insoles during walking on a flat ground showed validity compared to Pedar-X, and high reliability after repeated measurements.